2007
DOI: 10.1128/jb.01019-06
|View full text |Cite
|
Sign up to set email alerts
|

AccD6, a Member of the Fas II Locus, Is a Functional Carboxyltransferase Subunit of the Acyl-Coenzyme A Carboxylase in Mycobacterium tuberculosis

Abstract: The Mycobacterium tuberculosis acyl-coenzyme A (CoA) carboxylases provide the building blocks for de novo fatty acid biosynthesis by fatty acid synthase I (FAS I) and for the elongation of FAS I end products by the FAS II complex to produce meromycolic acids. The M. tuberculosis genome contains three biotin carboxylase subunits (AccA1 to -3) and six carboxyltransferase subunits (AccD1 to -6), with accD6 located in a genetic locus that contains members of the FAS II complex. We found by quantitative real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…Daniel et al confirmed that M. tuberculosis accD6 (accD6 Mtb ) is highly expressed during intensive mycolate biosynthesis and showed that the AccD6 and AccA3 proteins could together reconstitute an enzyme that is able to carboxylate acetyl-CoA in vitro (see Fig. S1 in the supplemental material) (18). However, due to the essential nature of accD6, the possible involvement of AccD6 in mycolic acid biosynthesis has never been addressed in vivo.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Daniel et al confirmed that M. tuberculosis accD6 (accD6 Mtb ) is highly expressed during intensive mycolate biosynthesis and showed that the AccD6 and AccA3 proteins could together reconstitute an enzyme that is able to carboxylate acetyl-CoA in vitro (see Fig. S1 in the supplemental material) (18). However, due to the essential nature of accD6, the possible involvement of AccD6 in mycolic acid biosynthesis has never been addressed in vivo.…”
mentioning
confidence: 82%
“…The expression profiles of all nine genes predicted to encode the carboxylase subunits of M. tuberculosis have been evaluated previously (18). Quantitative real-time PCR (qRT-PCR) analysis revealed that only the genes encoding the AccA3, AccD4, AccD5, and AccD6 carboxylase subunits were expressed at high levels during M. tuberculosis exponential growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AccA3–AccD5 have been shown to act mainly on propionyl‐CoA, producing methylmalonyl‐CoA, used for synthesis of methyl‐branched lipids, key components of the mycobacterial cell wall. AccA3–AccD6 acts mainly on acetyl‐CoA, producing malonyl‐CoA for fatty acid biosynthesis 11, 15, 21, 22.…”
mentioning
confidence: 99%